2017
DOI: 10.1002/jia2.25026
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with HIV testing among young men who have sex with men in Myanmar: a cross‐sectional study

Abstract: IntroductionIn Myanmar, men who have sex with men (MSM) experience high risk of HIV infection. However, access to HIV testing and prevention services remains a challenge among this marginalized population. The objective of this study was to estimate population prevalence and correlates of prior HIV testing among young MSM (YMSM) and informs the development of HIV testing and intervention programmes that respond to the specific needs of this population.MethodsFive hundred and eighty‐five YMSM aged 18 to 24 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 71 publications
5
16
1
Order By: Relevance
“…Awareness of sexual orientation is an important precursor to provider-initiated HIV testing [36], and non-disclosure of sexual behaviours may hinder the provision of relevant and tailored sexual health information, including assessments of eligibility for biomedical HIV prevention options. Our findings corroborate reports of differential levels of HIV vulnerability and access to HIV services among sexual identities in Myanmar [4,11,23,29] and support the need for HIV prevention strategies tailored to the specific needs of MSM and TW sub -populations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Awareness of sexual orientation is an important precursor to provider-initiated HIV testing [36], and non-disclosure of sexual behaviours may hinder the provision of relevant and tailored sexual health information, including assessments of eligibility for biomedical HIV prevention options. Our findings corroborate reports of differential levels of HIV vulnerability and access to HIV services among sexual identities in Myanmar [4,11,23,29] and support the need for HIV prevention strategies tailored to the specific needs of MSM and TW sub -populations.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, clients who did not report a testing history at baseline were 70% less likely to repeat test during the pilot period (OR: 0.29; 95% CI: 0.2 to 0.4), with no significant difference in risk behaviours between those who did and did not repeat test (data not reported). While MSM and TW in Myanmar self‐report high levels of regular HIV testing , the dissonance with data presented in this paper may suggest an overestimation of testing behaviours among MSM or TW, or ongoing barriers to enacting testing aspirations. Documented barriers to HIV testing among MSM and TW in Myanmar include experiences of stigma and discrimination, perceived unfriendliness of government or mainstream health staff, and avoidance of HIV prevention services manifestly catering for MSM and TW among those for whom concealment of sexual identity is a key priority .…”
Section: Discussioncontrasting
confidence: 60%
“…This finding is supported by studies conducted among both Myanmar and Chinese MSM. 21,43 The current study also revealed that those who engage in substance use are significantly more likely to have been recently tested for HIV. A possible explanation for this is that, as substance use is an effective method for MSM to overcome feelings of shame and internalized homophobia and to facilitate sexual behaviors, 44 users are more sexually active, and sexually active MSM are naturally more likely to undergo testing.…”
Section: Discussionsupporting
confidence: 53%
“…The two remaining factors included having two or more lifetime sexual partners and condom use during the last sexual intercourse. A higher number of sexual partners was reported to be associated with having an HIV test and with HIV infection prevalence in the general population and MSM [38, 39]. The results of the positive association between condom use and having an HIV test were consistent with those of studies among the general population in developing countries and among TB patients and MSM in Cambodia [10, 24, 25, 40], although a negative association between condom use with a noncommercial partner and having an HIV test was found in Cambodian FEWs [22].…”
Section: Discussionmentioning
confidence: 99%